The Politics of Syariatisation in Indonesia: MMI and GARIS' Struggle for Islamic Law - Lukito, Ratno (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
This paper addresses the deficiency of the doctrinal approach in Islamic legal studies. There is an emergent need to comprehend Islamic law from the standpoint of its practical aspects: that is, how the law is intended to produce certain results, whether it gives expected results, and whether an identifiable result is consistent with the reason for the law as one might have expected. This paper examines the discourse of legal Islamization from the perspective of its practical aspects, that is, how the idea is developed, campaigned, and impregnated in Muslim societies. A study of the organizations Majlis Mujahidin Indonesia (MMI) and Gerakan Reformis Islam (Garis) shows that both groups had different concerns. While MMI focused on the theoretical legal system, Garis was more concerned with the practical realm of law; yet the two are the same in orientation as they are both concerned with how everyday life is regulated for Muslims.